2015
DOI: 10.1021/tx500423m
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA and RNA Adduct Formation: Significantly Higher Levels of RNA than DNA Modifications in the Internal Organs of Aristolochic Acid-Dosed Rats

Abstract: Prolonged exposure to aristolochic acid (AA)contaminated slimming drugs and food is believed to be associated with the development of endemic nephropathy in Belgian women and in farmers living alongside the Danube River. Decades of research has revealed the pathophysiology of carcinogenesis of AA,and the molecular mechanisms underlying renal interstitial fibrosis remain unclear. We hypothesized that RNA modification may have contributed to the observed toxicity of AA. Thus, a highly sensitive and selective ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 36 publications
7
47
0
1
Order By: Relevance
“…In this regard, Leung and Chan [108] first described that AA forms covalently bonded RNA adducts both in vitro and in vivo. Particularly, AA have been found to modify guanosine at significantly higher frequencies than adenosine suggesting that guanosine is a major target of AA and that guanosine adducts might constitute a critical factor in AA-induced nephrotoxicity and carcinogenicity.…”
Section: Properties Of Aa and Mechanisms Of Nephrotoxicity And Carmentioning
confidence: 99%
“…In this regard, Leung and Chan [108] first described that AA forms covalently bonded RNA adducts both in vitro and in vivo. Particularly, AA have been found to modify guanosine at significantly higher frequencies than adenosine suggesting that guanosine is a major target of AA and that guanosine adducts might constitute a critical factor in AA-induced nephrotoxicity and carcinogenicity.…”
Section: Properties Of Aa and Mechanisms Of Nephrotoxicity And Carmentioning
confidence: 99%
“…In animal studies, A→T transversions were observed in the activating positions in H- ras of rats treated with AAs (Wang et al, 2011). Further, RNAs modified by AAs were at much higher frequencies than DNA (Leung and Chan, 2015).…”
Section: Toxicological Properties Of Aristolochic Acidsmentioning
confidence: 99%
“…Compared to adenine adducts, guanine adducts have been shown to be weakly miscoding, but whether dAMP can be misincorporated in vivo opposite dG-AAI when people are accidentally exposed to high doses of AA remains to be further investigated. It is worth mentioning that the alteration of guanosine by AA at a frequency significantly higher than with adenosine has been reported in kidney and liver tissues in AA-exposed rats suggesting that guanosine adducts with AA might play a more important role than hitherto believed in AA-induced toxicity [27]. Of note, A > G transitions as found in this Belgian series of AA patients, are not an unusual finding in AA-unrelated UC nor in other cancers [28].…”
Section: Discussionmentioning
confidence: 44%